2022
DOI: 10.1039/d1ta08252c
|View full text |Cite
|
Sign up to set email alerts
|

Single-atom-based catalysts for photoelectrocatalysis: challenges and opportunities

Abstract: Photoelectrocatalysis (PEC) has recently emerged as a promising strategy for utilizing solar energy due to its unique features in combining the merits of electrocatalysis and photocatalysis in solar energy harvesting,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 100 publications
0
21
0
Order By: Relevance
“…In recent years, single-atom catalysts have also been explored as co-catalysts to modify BiVO 4 photoanodes. Liu et al demonstrated through density functional theory (DFT) calculations that metal single-atom catalysts, such as Au, can provide BiVO 4 more surface active sites for OER . Zhang et al recently reported the modification of the Mo and W co-doped BiVO 4 (Mo,W:BiVO 4 ) photoanode by single Fe atom (Fe@NC) co-catalysts, and they found that the Fe ions have a conversion between Fe 2+ and Fe 3+ during PEC water splitting, which helps reduce the activation energy and promote the kinetics of OER .…”
Section: Modification Of Bivo4 For Pec Water Splittingmentioning
confidence: 99%
“…In recent years, single-atom catalysts have also been explored as co-catalysts to modify BiVO 4 photoanodes. Liu et al demonstrated through density functional theory (DFT) calculations that metal single-atom catalysts, such as Au, can provide BiVO 4 more surface active sites for OER . Zhang et al recently reported the modification of the Mo and W co-doped BiVO 4 (Mo,W:BiVO 4 ) photoanode by single Fe atom (Fe@NC) co-catalysts, and they found that the Fe ions have a conversion between Fe 2+ and Fe 3+ during PEC water splitting, which helps reduce the activation energy and promote the kinetics of OER .…”
Section: Modification Of Bivo4 For Pec Water Splittingmentioning
confidence: 99%
“…Similar to the majority of chemical transformation strategies, several catalysts have been fabricated and have exhibited superior catalytic properties for CO 2 utilization. [41][42][43] The most crucial issues call for innovations in catalytic systems through cost-efficient, high-activity, controlled selectivity, and long-term stability catalysts. [44][45][46] As a result, improving and adjusting catalytic materials have become the core in the study for CO 2 utilization technologies, with significant progress having been obtained at present.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to noble metal nanoparticles, single metal atoms with fully exposed active sites can improve the utilization of metals and greatly enhance the cost-effectiveness of the catalysts. 15 In addition, the interaction between the single metal atoms and the support enables the reformation of the electronic structure, enhancing the photocatalytic activity by promoting the transfer of photogenerated electrons. 16 Therefore, single metal atoms have been anchored on various catalysts to enhance their catalytic activity, such as metal oxides, 17 chalcogenides, 18 metal nitrides, 19,20 carbon materials, 21 metal–organic frameworks (MOFs), 22 and covalent–organic framework (COF) supports.…”
Section: Introductionmentioning
confidence: 99%